Association of chronic cough with exposure to polycyclic aromatic hydrocarbons in the US population - Miaomiao Jiang; Hui Zhao (Heliyon, 2024)
Polycyclic aromatic hydrocarbons (PAHs) are environmental pollutants formed during the incomplete combustion of organic substances, such as coal and oil. PAHs exposure is known to increase the incidence of respiratory diseases; however, limited research has focused on their impact on chronic cough. In this study, we utilized data from the National Health and Nutritional Examination Surveys (NHANES) from 2003 to 2012. Chronic cough was defined as 'coughing most days for three consecutive months or more'. Employing survey-weighted multivariate logistic regression models, we identified positive associations between all six PAHs metabolites (1-NAP, 2-NAP, 3-FLU, 2-FLU, 1-PHE, and 1-PYR) found in urine and the presence of chronic cough. Furthermore, results from restricted cubic spline modeling revealed a nonlinear relationship between urinary levels of 1-NAP, 2-NAP, 3-FLU, 2-FLU, and 1-PYR and the risk of chronic cough. Co-exposure modeling unveiled the combined effects of multiple exposures and the relative contributions of each PAHs. Notably, co-exposure to PAHs was positively associated with an increased risk of chronic cough, where 2-FLU emerged as the primary contributor to this association. These findings were particularly pronounced in individuals with high cotinine exposure (≥0.05 ng/mL). In conclusion, this study presents epidemiological evidence linking PAHs exposure to an elevated risk of chronic cough. Further prospective investigations are warranted to corroborate these findings.